Template-assisted synthesis of ruthenium oxide nanoneedles: electrical and electrochemical properties - Subhramannia, Mahima; Balan, Beena K.; Sathe, Bhaskar R.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K. (Journal of Physical Chemistry C, 2007)
We here demonstrate the formation of bundles of RuO2 nanoneedles (ca. 100 nm diameter) by a templateassisted electrodeposition from aqueous RuCl3 solution under potentiostatic conditions at room temperature. Cyclic voltammetric measurements in 0.5 M H2SO4 show significantly higher redox-related charging behavior for the RuO2 nanoneedles compared to that of the commercial sample, which is also supported by the electrochemical impedance data. A comparison of the specific capacitance reveals a higher value for nanoneedles (3 F/g instead of 0.4 F/g for the bulk), which has been explained on the basis of enhanced reactivity. More interestingly, electrical transport measurements reveal a transition from metallic to semiconducting behavior especially at low-temperature caused by an impurity scattering mechanism. We anticipate that the present simple route for the fabrication of RuO2 nanostructures will be useful to exploit their potentials in various fields such as electrocatalysis, nanoelectronics, and more importantly for designing supercapacitors.

Comparative study of the shape-dependent electrocatalytic activity of platinum multipods, discs, and hexagons: applications for fuel cells - Subhramannia, Mahima; Ramalyan, Kannan; Pillal, Vijayamohanan K. (Langmuir, 2008)
We here demonstrate a remarkable potential-dependent morphological evolution of platinum mesostructures in the form of multipods, discs, and hexagons using a porous anodic alumina membrane (PAAM). These structures prepared potentiostatically at -0.7, -0.5 and -0.3 V, respectively, reveal unique shape-dependent electrocatalytic activity toward both formic acid and ethanol oxidation reactions. A comparison of the electrooxidation kinetics of these structures illustrates that hexagons show better performance toward formic acid oxidation whereas, for ethanol oxidation, multipods show significantly enhanced activity. Interestingly, the enhancement factor (R) for these mesostructures with respect to that of commercial platinized carbon toward formic acid oxidation ranges up to 2000% for hexagons whereas for multipods and disc they are about 700% and 300%, respectively. Similarly, for ethanol oxidation, the calculated value of R varies up to 600% for multipods while for disc and hexagons these values are 500% and 200%, respectively. These shape-dependent electrocatalytic activity of Pt mesostructures have been further correlated with XRD results. Thus, the present results demonstrate the importance of precise control of morphology by an electric field and their potential benefits especially for fuel cell applications since designing a better electrocatalyst for many fuel cell reactions continues to be an important challenge.

Shape-dependent electrocatalytic activity of platinum nanostructures - Subhramannia, Mahima; Pillai, Vijayamohanan K. (Journal of Materials Chemistry, 2008)
Since many metallic nanostructures with different shapes exhibit unique chemical and physical properties, a systematic attempt to synthesize these shape-controlled structures for property-shape correlation remains an important challenge in contemporary materials chemistry. Main difficulties like poor shape selectivity, low yield, presence of impurity phases, difficulty of separation, etc., are exacerbated since metallic structures have high surface energies which favour lower surface areas, and consequently many synthesis strategies, including the use of hard and soft templates and external nucleating agents, are being employed along with theoretical guidelines from density functional calculations on simpler systems. One of the important application areas where these structures have gained profound attention is in electrocatalysis, where the kinetics of many structure-sensitive reactions of technological relevance have been experimentally observed to show drastic changes with shape especially in the nanosize domain, at least in one dimension. Considering their scientific and technological importance, this feature article provides an overview of the recent progress on the shape-controlled synthesis of metallic nanostructures with special emphasis on platinum, and their crucial role in the electrocatalysis of anodic reactions for polymer electrolyte fuel cells.

Y-junction nanostructures of palladium: enhanced electrocatalytic properties for fuel cell reactions - Subhramannia, Mahima; Ramaiyan, Kannan; Aslam, Mohammed; Pillai, Vijayamohanan K. (Journal of Electroanalytical Chemistry, 2009)
Here we demonstrate the utility of hierarchically designed alumina templates for the formation of palladium Y-junction nanostructures through a chemical vapor deposition route. These structures exhibit enhanced electrocatalytic activity for the oxidation of formic acid (up to 1020%) compared to that of platinum Y-junction nanostructures, which could be of immense relevance to portable fuel cell technology, since designing a better electrocatalyst for fuel cell reactions continues to be an important challenge. Apart from the obvious applications in fuel cell electrocatalysis, these Y-junction nanostructures could also act as promising candidates for room temperature hydrogen separation and more importantly as interconnects in molecular scale electronic devices. The present method of fabrication of Y-junction nanostructures using hierarchical alumina templates could be extended to other metallic/semiconducting systems facilitating more general opportunities for such hierarchical designs in nanoelectronics. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: electrocatalysts; fuel cells; Hierarchical structures; Nanostructure; Porous alumina membrane; Y-junctions